ANALISIS REALISASASI PENDAPATAN ASLI DAERAH DARI SEKTOR PAJAK DAERAH SEBELUM DAN SESUDAH PANDEMI PADA KABUPATEN LAMPUNG UTARA - R Weddie Andriyanto (Jurnal Akuntansi dan Keuangan (JAK), 2023)
The purpose of this study was to determine the impact of the pandemic on the realization of local revenue from the regional tax sector in North Lampung Regency. The data in this study is secondary data obtained from the BPPRD Office of North Lampung Regency. The number of research samples is 22 samples. The data used is secondary data. The tests carried out were descriptive statistical tests, normality tests, and the Wilcoxon signed rank test. Analysis of the data used to test the hypothesis is to use the analysis technique of pairwise different sample test. The results of this study indicate that there are no significant differences in the realization of local revenue from the regional tax sector in North Lampung Regency before and after pandemic.